Status of herbicide resistance in Phalaris minor in wheat in Haryana - SINGH, RAGHUVEER; YADAV, DHARAM BIR; SHARMA, RAMAN; SHARMA, SAURAV (The Indian Journal of Agricultural Sciences, 2021)
Herbicide resistance in little seed canary grass (Phalaris minor Retz.) in wheat is the major sustainability issue, which puts the rice-wheat (R-W) system in north-western Indo-Gangetic Plains (IGP) under serious threat. To assess the resistance level, a questionnaires based survey with a systematic approach was conducted during rabi 2017-18 in five districts (Yamuna Nagar, Kaithal, Karnal, Fatehabad and Rohtak) of Haryana. The study revealed that at present, farmers of Haryana are closely back to square one, similar to the situation of herbicide resistance in P. minor like 1990’s and currently, no herbicide is satisfactorily effective against resistant P. minor. Farmers are using every possible combination of herbicides in a hit and trial way. In 2017-18, half of the farmers (50%) went for the second spray, 13% applied the third spray, and even 3% of farmers opted for the fourth spray. The same pattern followed in the case of herbicide dose; in 2017-18, 38% of farmers opted for 2-4 X-dose, 16% of farmers for 4-6 X-dose, 3% of farmers for 6-8 X-dose, and even one percent farmers applied 8-10 X-dose. Negative relationship between percent control with higher dose (X) (Chi-Square value 72.560a, DF = 12 and p = <0.001) and multiple sprays (Chi-Square 67.076a, DF = 8 and P = <0.001) recorded during 2017-18 also indicates strong chances/evidences of herbicide resistance development.